Review of â€œThe dimensions of an instructional design knowledge base: Theory, research, and practiceâ€ - Warkineh, Turuwark Zalalam; Gizaw, Abiy Menkir; Kelkay, Asrat Dagnew (Bahir Dar Journal of Education, 2024)
This review assesses the book titled "The instructional design knowledge base: Theory, research, and practice" authored by Richey, Klein, and Tracy, highlighting its emphasis on foundational knowledge, extensive theory base, and application to current Instructional Design (ID) practices. The book offers a comprehensive overview of ID theories from various disciplines, making it valuable for scholars, graduate students, educators, and practitioners in the field. It also guides decision-making and includes suggestions for future research, making it beneficial for researchers aiming to contribute to the field of ID.